The great (Australian) property crime decline1. Issue 3 (October 2016) - Weatherburn, Don; Halstead, Imogen; Ramsey, Stephanie
Abstract: Between 1973/74 and 2000, rates of robbery, break and enter, motor vehicle theft and most other major forms of theft rose almost without interruption. Between 2000 and 2009, recorded rates of robbery in Australia fell by 63 per cent, recorded rates of burglary fell by 57 per cent, recorded rates of motor vehicle theft fell by 62 per cent, and recorded rates of all other forms of theft fell by 37 per cent. This article considers possible explanations for the fall in theft and robbery in light of the available evidence. It argues that a reduction in heroin dependence, improvements in economic outcomes, increases in the risk of arrest and imprisonment, and improved vehicle security are likely to have been significant contributors to the decline.